Creativity at the crossroads? The creative industries in Western Australia - Dockery, Michael; Duncan, Alan; Hailemariam, Abebe; Salazar, Silvia; Seymour, Richard (2021)
This report, the sixth in the Focus on Industry series provides an in-depth look at the arts and cultural sectors within the Western Australian economy.